2008
DOI: 10.1243/09544054jem1295
|View full text |Cite
|
Sign up to set email alerts
|

Designing for ‘use phase’ energy losses of domestic products

Abstract: This approach being proposed is based on the principle of understanding and establishing the two kinds of energy losses for products, the first kind of losses, caused by the engineering design, materials and technology used in construction of the product will be called the intrinsic losses. Mennink et al. [3] carried out a series of tests on a 200 litre refrigerator to determine where the largest sources of energy losses were in the device. The product they tested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Design for sustainable behaviour is emerging as a research area at the intersection of sustainable design and interaction design, applying insights from multiple disciplines to the problems of influencing more environmentally friendly use of products, services and environments (e.g., Combe et al, 2010;van Dam et al, 2010;Froehlich et al, 2010;Elias et al, 2009;Matsuhashi et al, 2009;Lilley, 2009;Bhamra et al, 2008;Pettersen and Boks, 2008;Wever et al, 2008;Lockton et al, 2008;Rodriguez and Boks, 2005). However, as Blevis (2007) puts it, "[i]t is easier to state the kinds of behaviours we would like to achieve from the perspective of sustainability than it is to account for how such behaviours may be adequately motivated".…”
Section: Introduction: Design For Sustainable Behaviourmentioning
confidence: 99%
“…Design for sustainable behaviour is emerging as a research area at the intersection of sustainable design and interaction design, applying insights from multiple disciplines to the problems of influencing more environmentally friendly use of products, services and environments (e.g., Combe et al, 2010;van Dam et al, 2010;Froehlich et al, 2010;Elias et al, 2009;Matsuhashi et al, 2009;Lilley, 2009;Bhamra et al, 2008;Pettersen and Boks, 2008;Wever et al, 2008;Lockton et al, 2008;Rodriguez and Boks, 2005). However, as Blevis (2007) puts it, "[i]t is easier to state the kinds of behaviours we would like to achieve from the perspective of sustainability than it is to account for how such behaviours may be adequately motivated".…”
Section: Introduction: Design For Sustainable Behaviourmentioning
confidence: 99%
“…In order to effectively tackle this task, designers require knowledge of user behaviour: how they use refrigerators, the rationale for their actions, and where/when inefficient use occurs. These behaviours were collected and discussed by Elias et al (2009) and have been used to inform the various types of information stimuli presented to the teams. A more detailed analysis of the primary experimental results will be presented elsewhere.This study was selected as it represented a typical small-scale design research study (see Section 1).…”
mentioning
confidence: 99%
“…According to Elias et al, user-related losses constitute a significant share of the energy use by domestic products. Such losses are also likely to increase in proportion as technological development of appliances continues to reduce intrinsic energy losses from, for instance, poor insulation or excess heat [15]. Hager and Morawicki highlighted the need to address user behavior and practices to reduce the environmental impact of cooking [16], and Hobman et al identified the category of household kitchen practices as one of the most promising areas for behavior change in the home [17].…”
Section: Introductionmentioning
confidence: 99%